Natural polysacarides as an experimental therapeutic approach to the gastrointestinal tract: a systematic review (Research, Society and Development, 2021)
The purpose of this study is to conduct a systematic literature review on the main effects of natural polysaccharides extracted from plants and algae in experimental models of gastrointestinal disorders (GID). This review focuses on recent advances in experimental studies with natural polysaccharides for the treatment of gastroesophageal reflux disease (GERD), gastritis, colitis, and diarrhea. This is a bibliographical research based on a qualitative approach, considering the procedures for analyzing and interpreting the data obtained, carried out through searches in the following databases: Medical Literature Analysis and Retrievel System Online (Medline), Scientific Electronic Library Online (Scielo) and the National Library of Medicine of the United States (PubMed), using the descriptors: gum, sulfated polysaccharide, polysaccharide, gastric damage, antidiarrheal, gastroesophageal reflux and colitis in different combinations using the Boolean operator “and”. The works inserted in this study were only those available in the platforms and classified as articles, theses and dissertations, included and indexed between 2011 and 2021, which had as their principal methodology experimental and preclinical studies in the spectrum of activities in vitro and in vivo about the effects of natural polysaccharides in models of gastrointestinal disorders. The final sample was composed of  35 papers, as studies that did not fit these criteria were unconsidered. The mechanisms and the effectiveness of polysaccharides are minutely presented and discussed. In general, because of their anti-inflammatory, antioxidant, gastroprotective and antidiarrheal properties, demonstrating satisfactory efficacy and safety, studies suggest that natural polysaccharides are an interesting alternative for the development of innovative therapies for GID.